Impact of Rocky Desertification Control on Soil Bacterial Community in Karst Graben Basin, Southwestern China - Li, Qiang; Song, Ang; Yang, Hui; Müller, Werner E. G. (Frontiers in Microbiology, 2021)
Microorganisms play critical roles in belowground ecosystems, and karst rocky desertification (KRD) control affects edaphic properties and vegetation coverage. However, the relationship between KRD control and soil bacterial communities remains unclear. 16S rRNA gene next-generation sequencing was used to investigate soil bacterial community structure, composition, diversity, and co-occurrence network from five ecological types in KRD control area. Moreover, soil physical-chemical properties and soil stoichiometry characteristics of carbon, nitrogen and phosphorus were analyzed. Soil N and P co-limitation decreased in the contribution of the promotion of KRD control on edaphic properties. Though soil bacterial communities appeared strongly associated with soil pH, soil calcium, soil phosphorus and plant richness, the key factor to determine their compositions was the latter via changed edaphic properties. The co-occurrence network analysis indicated that soil bacterial network complexity in natural ecosystem was higher than that in additional management ecosystem. Candidatus Udaeobacter, Chthoniobacterales and Pedosphaeraceae were recognized as the key taxa maintaining karst soil ecosystems in KRD control area. Our results indicate that natural recovery is the suitable way for restoration and rehabilitation of degraded ecosystems, and thus contribute to the ongoing endeavor to appraise the interactions among soil-plant ecological networks.